Foundations of sustainable construction management with international benchmarking - AbdulLateef Olanrewaju (Sustainable Futures)
The global push for sustainable construction has highlighted significant gaps in integrating sustainability elements into construction management. While the supply of sustainable construction is struggling to keep pace with the growing demand, the value added of sustainable construction is not meeting the requirements of stakeholder's value systems. Despite the urgency, there is a lack of comprehensive framework addressing how to manage these elements effectively. This predicament is primarily attributable to the inadequacies in the practices, processes, tools, and strategies employed across all the phases of the sustainable construction projects. This research fills this gap by developing an international framework for sustainable construction management through clustering of its critical success factors (CSFs) using principal component analysis (PCA). Primary data for the research were collected based on survey questionnaires that were administered to more than 600 construction companies. The survey contains 48 CSFs for sustainable construction management. The PCA clustered the CSFs into nine principal components comprising project management structure, procurement plan, environmental ethics, sustainable construction managers, company policy, information management, health and safety plan, digitisation, and community engagement. This study pioneers an international framework for sustainable construction management. The findings hold significant implications for both future research and practical policy development in sustainable construction. As sustainability requirements and technologies evolve, future works should focus on refining the framework and exploring its application in emerging contexts.